1980
DOI: 10.1159/000241255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hypo- and Hyperthyroidism on Noradrenaline Metabolism in Brown Adipose Tissue of the Developing Rat

Abstract: We studied the noradrenaline content, and monoamine oxidase (MAO) and catechol-O-methyltransferase (COMT) activities in brown adipose tissue (BAT) of normal, hypothyroid, and hyperthyroid developing rat. In the newborn, thyroid hormones are necessary for the increase in noradrenaline content which occurs between 0 and 5 days. Hypothyroidism increases both MAO and COMT activities. Hyperthyroidism decreases MAO activity but not noradrenaline content or COMT activity. In the full-term fetus, hypothyroidism decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In this respect, the decrease we have found in the intensity of this uptake in the young hypothyroid animals could be fol lowed by a lessening in the entrance rate of the transmitter in the tissue, and this could, then, partially explain why the norepineph rine content is lower in ISBAT of these hypo thyroid rats [11].…”
Section: Uptake O F Norepinephrinementioning
confidence: 69%
See 2 more Smart Citations
“…In this respect, the decrease we have found in the intensity of this uptake in the young hypothyroid animals could be fol lowed by a lessening in the entrance rate of the transmitter in the tissue, and this could, then, partially explain why the norepineph rine content is lower in ISBAT of these hypo thyroid rats [11].…”
Section: Uptake O F Norepinephrinementioning
confidence: 69%
“…In a previous report [11], we described an inhibition of the neonatal increase in ISBAT norepinephrine content after chemical thy roidectomy. In the same animals, the activi ties of the two major enzymes of norepineph rine catabolism, monoamine oxidase and catechol-O-methyltransferase were increased as compared to control animals.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Because of hypothyroidism or independent of this the BAT mass with its thermogenic capacity is poorly developed [2]. It is concluded that promising measures to improve the health and life expectancy of nude mice -apart from con trolling infectious diseases -would be to pro vide a warmer environment (Ta 30-32 °C) and thyroid hormone substitution.…”
Section: Discussionmentioning
confidence: 99%